Pyrite and sphalerite trace element redistribution during metamorphism of the Rävliden North VMS deposit, northern Sweden - Rincon, Jonathan; Jansson, Nils F.; Thomas, Helen; Kaiser, Majka C.; Persson, Mac F.; Simán, Filip; Wanhainen, Christina (Luleå tekniska universitet, Geovetenskap och miljöteknik, 2022)
The Rävliden North volcanogenic massive sulphide (VMS) deposit and its host rocks exhibit a shared history of metamorphism during the 1.88–1.86 Ga deformation phases of the Svecokarelian orogeny. Predominantly internal sulphide remobilisation produced minor modifications to the overall pre-metamorphic trace element distribution including remobilisation. Post-Svecokarelian sulphide-bearing zeolite- and calcite veinlets cross-cut the stratigraphic hanging wall suggesting mobilisation of sulphides in a fluid phase during an overprinting later event unrelated to the VMS mineralisation. ISBN för värdpublikation: 978-91-987833-0-8